Kewenangan Mengadili atas Penerapan Choice Of Law Pada Asuransi Pengangkutan Laut - Ni Made Debi Ade Viskesia; I Nyoman Putu Budiartha; I Putu Gede Seputra (Warmadewa Press, 2021)
Transportation is currently developing very rapidly in the aspect of life, there are many transportations that provide cheaper prices than other transportation. To avoid the risks in sea transportation using sea freight insurance, but sea freight insurance still uses English law and its provisions. So that in the sea transportation insurance agreement the choice of law applies. The study examines the position of the choice of law in the settlement of maritime transportation disputes and explains the procedure for resolving disputes over the choice of law on the authority to adjudicate sea transportation. This study uses a normative research method with a statutory approach because there is still a conflict of norms, sourced from primary and secondary data. In the Civil Code Articles 1320 and 1338 it has been determined that the conditions for the validity of an agreement and agreements made legally will become law for those who make them. So apart from that, the choice of law in the jurisdiction to adjudicate is also contained in international civil law, thus in the settlement of maritime transportation insurance disputes that still use English law, it can be resolved by looking at the facts contained in the sea freight insurance agreement with the applicable laws. apply.